2001
DOI: 10.1007/s004170100262
|View full text |Cite
|
Sign up to set email alerts
|

Topological–histological investigation of the pterygium

Abstract: Histological alterations of the stroma predominate quantitatively over those of the epithelium. The topographical anatomy of the lesion and the fact that bulbar tissue is modified along with the pterygium should be taken into account when excision is undertaken. We predict that if all the altered tissue is removed, the rate of recurrence will be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
(35 reference statements)
2
14
0
1
Order By: Relevance
“…In the current study, we confirmed the presence of the lobes of pterygium stromal tissue that projected sideways from the continuous base of the pterygium, a pattern that was described also by Seifert et al 2001(Seifert et al 2001.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the current study, we confirmed the presence of the lobes of pterygium stromal tissue that projected sideways from the continuous base of the pterygium, a pattern that was described also by Seifert et al 2001(Seifert et al 2001.…”
Section: Discussionsupporting
confidence: 86%
“…Asterisks indicate the creeping conjunctival stroma of the pterygium. Seifert et al 2001 who studied the topological and histological patterns of the pterygium. In their study, they proved histologically the presence a narrow strip of newly formed layer of pathological pterygium stroma lying between the corneal epithelium and the Bowman's membrane beyond the end of the pterygium boundaries, and this finding was also clearly demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This activation may cause 1) phenotypic alterations in a distinct population of epithelial cells, 2) production of proinflammatory and angiogenic cytokines 7 and growth factors, 8 and 3) increased invasiveness due to enhanced production of matrix metalloproteinases (MMPs) over and above their natural tissue inhibitors (TIMPs). 6,9 -12 To date, we 6,9 -12 and others [13][14][15][16][17] have accumulated data from in vitro culture and in vivo tissue-based studies that resemble investigations performed in human UVexposed skin. These studies have demonstrated increased MMPs in human skin and skin-derived cells in response to UV radiation.…”
mentioning
confidence: 99%
“…Seifert et al (24) by using conventional staining procedure (hematoxylin-eosin, alcian blue and toluidine blue) demonstrated the presence of many large-diameter lymphatic vessels in a markedly edematous human pterygium and more recently Pérez-Rico et al (6) showed the expression of fibulin-2 and fibulin-3 in the subepithelial connective tissue of human pterygium distributed along blood and lymphatic vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available concerning lymphangiogenesis in the cornea and the presence of lymphatic vessels in pterygium (24). The aim of this study was to evaluate by immunohistochemistry, by using antibodies against D2-40 and Prox-1, the presence of lymphatic vessels in human pterygium.…”
Section: Introductionmentioning
confidence: 99%